2009
DOI: 10.1111/j.1439-0507.2009.01717.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study: optical coherence tomography as a non-invasive diagnostic perspective for real time visualisation of onychomycosis

Abstract: The objective of this study was to compare optical coherence tomography (OCT) with conventional techniques such as KOH-preparation, culture and histology in the identification of the fungal elements in the nail. A total of 18 patients were examined; 10 with clinically evident onychomycosis in toe nails, two with psoriatic nail lesions, one with nail affection caused by lichen planus and five healthy controls. Serial in vivo OCT analyses of onychomycosis was performed prior to KOH-preparation, culture and punch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
2
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 23 publications
0
38
2
6
Order By: Relevance
“…Two small OCT studies in HCs described the appearance of the nail using OCT; these mentioned leuconychia with a similar pattern to that which we have noted [22,29]. One other study assessed patients with a variety of nail disorders [30]. This included two patients with psoriatic nail disease, with the first description of the appearance of nail pitting.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Two small OCT studies in HCs described the appearance of the nail using OCT; these mentioned leuconychia with a similar pattern to that which we have noted [22,29]. One other study assessed patients with a variety of nail disorders [30]. This included two patients with psoriatic nail disease, with the first description of the appearance of nail pitting.…”
Section: Discussionmentioning
confidence: 74%
“…Recent studies have shown some potential for the use of OCT in the diagnostic assessment of fungal nail disease, with good sensitivity but lower specificity than other methods [30,31]. In a separate study, a change in nail thickness has been demonstrated using OCT after exposure to water [29].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were consistent with our results of healthy control patients, with nail thickness falling within this range. Abuzahra et al [17] distinguished nail psoriasis from onychomycosis. Unlike nail psoriasis, which consists of homogeneous scattering within the nail plate, onychomycosis contains a high scattering area surrounded by a low scattering area, indicating the presence of fungus.…”
Section: Discussionmentioning
confidence: 99%
“…In-vivo diagnosis of alopecia; follow-up of same hairs; no epilation/shaving needed; results comparable to histology [ 16 ] Nail diagnosis Fungal elements may be visualized in the usually homogeneous, low-signal nail plate [ 17 ] ; currently no differentiation of pathogens; differentiation from inflammatory causes of nail changes such as lichen ruber, psoriasis, atopic dermatitis…”
Section: Hair Analysismentioning
confidence: 99%